The application of the Dhiana Setyorini Score Card in early detection of the risk of preeclampsia - Syaiful, Syaiful; Nurwahidah, Nurwahidah; Lalu, Sulaiman (International Journal of Public Health Science (IJPHS), 2025)
Preeclampsia pregnancy complications can negatively impact the fetal in the womb, potentially leading to delayed or non-developmental growth. This study aimed to determine the effect of the application of the Dhiana Setyorini Score Card on the early detection of preeclampsia risk. The study employed a quasi-experimental design, with an intervention group receiving the Dhiana Setyorini Score Card and a control group receiving counselling on preeclampsia. The study utilized purposive sampling with 100 cadres divided into two groups, focusing on four health centers in Bima, Indonesia, and analyzed using the Mann-Whitney test. Knowledge in the intervention group increased significantly in both knowledge and ability categories. However, in the control group, knowledge and ability did not differ significantly. The application of the Dhiana Setyorini Score Card in the intervention group was better than counselling conducted by the health center for the early detection of preeclampsia. There was a significant difference between the levels of knowledge and ability in the intervention group (p<0.005). In conclusion, the application of the Dhiana Setyorini Score Card is more effective in increasing knowledge and the ability to detect preeclampsia early than the counselling method conducted by a health center.